Comparison of Mometasone Furoate Monohydrate (Nasonex) and Fluticasone Propionate (Flixonase) Nasal Sprays in the Treatment of Dust Mite-sensitive Children with Perennial Allergic Rhinitis - Ka-Kit Mak; Min-Sho Ku; Ko-Hsiu Lu; Hai-Lun Sun; Ko-Huang Lue (Elsevier, 2013)
Various studies have investigated the efficacies of mometasone furoate monohydrate (MFM) and fluticasone propionate (FP) nasal sprays for adults. However, research on their effectiveness for children is limited. This study compares the efficacies of MFM and FP nasal sprays in pediatric patients with perennial-allergic rhinitis. Materials and methods: For this study, 94 perennial allergic rhinitis patients aged 6-12 years were randomly assigned to two treatment groups: an MFM group and an FP group. Treatment was provided for 4 weeks. The effects of the two agents were compared using the Pediatric Rhinoconjunctivitis Quality of Life Questionnaire and total symptom scores (TSSs). Nasal-peak expiratory flow rates and eosinophil percentage in nasal smears were also compared between the two groups. Results: Patients in the MFM group exhibited significant improvement in their TSS (t = −2.65, p < 0.05). A detailed TSS analysis showed MFM to be more effective for relieving nasal symptoms, whereas FP was more effective for relieving non-nasal symptoms. Patient questionnaire scores suggested a significant reduction in symptoms for both the MFM (t = −7.23, p < 0.01) and FP (t = −5.43, p < 0.01) groups. The flow rate test results indicated significant improvements in the MFM group (t = 2.27, p < 0.05). Conclusion: Following the 4-week therapy, MFM provided greater improvement compared to FP for symptoms of childhood perennial-allergic rhinitis. Based on their TSSs, the MFM group experienced more effective relief of nasal symptoms, whereas the FP group experienced more effective relief of non-nasal symptoms.